Protein Energy-Malnutrition: Does the In Vitro Zinc Sulfate Supplementation Improve Chromosomal Damage Repair? - Padula, Gisel (2014)
Protein-energy malnutrition (PEM) is originated by a cellular imbalance between nutrient/energy supply and body’s demand. Induction of genetic damage by PEM was reported. The purpose of this study was to determine the genetic effect of the in vitro zinc sulfate (ZnSO4) supplementation of cultured peripheral blood lymphocytes from children with PEM. Twenty-four samples from 12 children were analyzed. Anthropometric and biochemical diagnosis was made. For the anthropometric assessment, height-for-age index, weight-for-age index, and weight-for-height index were calculated (WHO, 2005). Micronutrient status was evaluated. A survey for assessed previous exposure to potentially genotoxic agents was applied. Results were statistically evaluated using paired sample t test and χ2 test. Each sample was fractionated and cultured in two separate flasks to performed two treatments. One was added with 180 μg/dl of ZnSO4 (PEMs/ZnSO4) and the other remains non-supplemented (PEMs). Cytotoxic effects and chromosomal damage were assessed using the cytokinesis-block micronucleus assay (CBMN). All participants have at least one type of malnutrition and none have anemia, nor iron, folate, vitamin A, and zinc deficiency. All PEMs/ZnSO4 samples have a significant reduction in the micronucleus (MNi) frequency compared with PEMs (t=6.25685; p<0.001). Nuclear division index (NDI) increase in PEMs/ZnSO4 (t=−17.4226; p<0.001). Nucleoplasmic bridge (NPBs) frequency was four times smaller in PEMs/ZnSO4 (χ2 =40.82; p<0.001). No nuclear buds (NBuds) were observed. Cytotoxic effects and chromosomal damage observed in children suffering from PEM can be repaired in vitro with zinc sulfate supplementation.